PHILOLOGICAL STUDY AND HADITH CRITICISM OF THE MANUSCRIPT SABIL AL-SALAM LI-BULUGH AL-MARAM BY MUHAMMAD IDRUS QAYM AL-DIN (c. 1784-1851) - Faiz, Muhammad; Jamaludin, Fitah; Firdaus, Achmadana Syachrizal Muziburrochman; Masruri, Muhammad (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2026)
This article examines Sabīl al-Salām li-Bulūgh al-Marām by Muḥammad Idrus Qaym al-Dīn al-Buṭūnī through an integrated philological and hadith-critical approach. The study is motivated by a broader academic problem, namely the limited scholarship on Nusantara hadith manuscripts that moves beyond descriptive cataloguing toward critical text reconstruction and analysis of hadith transmission practices. Previous studies have identified the manuscript’s general characteristics and its intertextual relation to Bulūgh al-Marām, yet they have not adequately explained how the text was constructed, how hadith materials were selected and cited, and what this reveals about the manuscript’s intellectual and pedagogical function. The manuscript itself contains 233 hadiths distributed across 13 chapters, but this article focuses on the reconstruction of the text and on selected hadiths from its opening chapters as an entry point for examining patterns of quotation, source attribution, and textual variation. Methodologically, the article combines philological reconstruction, transliteration, takhrīj, and comparative hadith analysis. The findings show that the manuscript contains a number of textual inconsistencies and abbreviated citation forms that make critical editing necessary. The study also indicates that the cited hadiths should not be read merely as isolated reports for sanad evaluation, but as part of a selective pedagogical compilation reflecting the scholarly orientation of its author. This article argues that Sabīl al-Salām li-Bulūgh al-Marām is significant not only as a historical manuscript, but also as evidence of how hadith was transmitted, adapted, and taught in nineteenth-century Buton. Further study of the full corpus of 233 hadiths is needed to clarify the manuscript’s overall citation pattern, source preference, and distribution of hadith quality. [Artikel ini mengkaji manuskrip Sabīl al-Salām li-Bulūgh al-Marām karya Muḥammad Idrus Qaym al-Dīn al-Buṭūnī melalui pendekatan terpadu antara filologi dan kritik hadis. Penelitian ini berangkat dari persoalan akademik yang lebih luas, yaitu masih terbatasnya kajian terhadap manuskrip hadis Nusantara yang melampaui deskripsi katalogis menuju rekonstruksi teks kritis dan analisis praktik transmisi hadis. Kajian-kajian terdahulu telah mengidentifikasi karakter umum manuskrip dan hubungan intertekstualnya dengan Bulūgh al-Marām, tetapi belum menjelaskan secara memadai bagaimana teks tersebut disusun, bagaimana hadis-hadis dipilih dan disitir, serta apa maknanya bagi fungsi intelektual dan pedagogis manuskrip. Manuskrip ini memuat 233 hadis yang tersebar dalam 13 bab, tetapi artikel ini difokuskan pada rekonstruksi teks dan analisis terhadap hadis-hadis terpilih pada bab-bab awal sebagai pintu masuk untuk menelaah pola kutipan, penyebutan sumber, dan variasi tekstual. Secara metodologis, artikel ini menggabungkan rekonstruksi filologis, transliterasi, takhrīj, dan analisis hadis komparatif. Hasil penelitian menunjukkan bahwa manuskrip ini memuat sejumlah ketidakkonsistenan tekstual dan bentuk sitasi yang ringkas sehingga penyuntingan kritis menjadi langkah yang diperlukan. Kajian ini juga menunjukkan bahwa hadis-hadis yang dikutip tidak semata-mata perlu dibaca sebagai laporan individual untuk penetapan sanad, tetapi sebagai bagian dari kompilasi pedagogis yang selektif dan mencerminkan orientasi keilmuan penulisnya. Artikel ini menegaskan bahwa Sabīl al-Salām li-Bulūgh al-Marām penting bukan hanya sebagai manuskrip historis, tetapi juga sebagai bukti praktik transmisi, adaptasi, dan pengajaran hadis di Buton pada abad ke-19. Penelitian lanjutan terhadap keseluruhan korpus 233 hadis masih diperlukan untuk menjelaskan secara lebih utuh pola sitasi, preferensi sumber, dan distribusi kualitas hadis di dalamnya.]